Regulation of Yujin Powder alcoholic extracts on ILC3s-TD IgA-colonic mucosal flora axis of DSS-induced ulcerative colitis - Wen, Yanqiao; Zhang, Wangdong; Yang, Rong; Jiang, Lidong; Zhang, Xiaosong; Wang, Baoshan; Hua, Yongli; Ji, Peng; Yuan, Ziwen; Wei, Yanming; Yao, Wanling (Frontiers in Microbiology, 2022)
The intestinal flora maintained by the immune system plays an important role in healthy colon. However, the role of ILC3s-TD IgA-colonic mucosal flora axis in ulcerative colitis (UC) and whether it could become an innovative pathway for the treatment of UC is unknown. Yujin Powder is a classic prescription for treatment of dampness-heat type intestine disease in traditional Chinese medicine and has therapeutic effects on UC. Hence, the present study aimed to investigate the regulatory mechanism of Yujin Powder alcoholic extracts (YJP-A) on UC via ILC3s-TD IgA-colonic mucosal flora axis. The UC mouse model was induced by drinking 3.5% dextran sodium sulfate (DSS), meanwhile, YJP-A was given orally for prevention. During the experiment, the clinical symptoms of mice were recorded. Then the intestinal injury and inflammatory response of mice about UC were detected after the experiment. In addition, the relevant indicators of ILC3s-TD IgA-colonic mucosal flora axis were detected. The results showed that YJP-A had good therapy effects on DSS-induced mice UC: improved the symptoms, increased body weight and the length of colon, decreased the disease activity index score, ameliorated the intestinal injury, and reduced the inflammation etc. Also, YJP-A significantly increased the ILC3s proportion and the expression level of MHC II; significantly decreased the proportion of Tfh cells and B cells and the expression levels of Bcl6, IL-4, Aicda in mesenteric lymph nodes of colon in UC mice and IgA in colon. In addition, by 16S rDNA sequencing, YJP-A could restore TD IgA targets colonic mucus flora in UC mice by decreasing the relative abundance of Mucispirillum, Lachnospiraceae and increasing the relative abundance of Allprevotella, Alistipes, and Ruminococcaceae etc. In conclusion, our results demonstrated that the ILC3s-TD IgA-colonic mucosal flora axis was disordered in UC mice. YJP-A could significantly promote the proliferation of ILC3s to inhibit Tfh responses and B cells class switching through MHC II, further to limit TD IgA responses toward colonic mucosal flora. Our findings suggested that this axis may be a novel and promising strategy to prevent UC.